1993
DOI: 10.1172/jci116357
|View full text |Cite
|
Sign up to set email alerts
|

Role of AT1 receptors in the resetting of the baroreflex control of heart rate by angiotensin II in the rabbit.

Abstract: Angiotensin II (Ang II) resets the baroreflex control of heart rate to a higher blood pressure. This action is apparently mediated via Ang II receptors in the area postrema, but it is not known if these are of the AT, or AT2 subtype. In the present study the effects of losartan, a selective AT, receptor antagonist, and PD 123319, a selective AT2 antagonist, on the cardiac baroreflex response to Ang II were investigated in conscious rabbits with chronically implanted arterial and venous catheters. Baroreflex cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 32 publications
4
33
0
2
Order By: Relevance
“…She demonstrated that angiotensin-induced baroreflex resetting was partially reversed soon after angiotension II infusion was stopped despite maintenance of the hypertensive state with infusions of phenylephrine or methoxamine. Although the exact mechanism of baroreflex resetting by angiotension II is unknown, it is thought to involve central nervous system actions via AT-1 receptors at the level of the area postrema (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…She demonstrated that angiotensin-induced baroreflex resetting was partially reversed soon after angiotension II infusion was stopped despite maintenance of the hypertensive state with infusions of phenylephrine or methoxamine. Although the exact mechanism of baroreflex resetting by angiotension II is unknown, it is thought to involve central nervous system actions via AT-1 receptors at the level of the area postrema (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intravenous administration of losartan (10 mg/kg/d) to normal rats for 10 d blocked Ang II action and lowered the blood pressure (7). Dizziness was reported as a side effect of losartan in clinical treatment (25,26). However, the mechanism of the losartan-induced lowering effect on normal blood pressure was not elucidated in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Each drug was administered once daily for 6 days either alone or in combination in a crossover fashion. Blood samples for concentration measurements were taken before the first dose and the fifth dose and at 0, 0.25, 0.5, 0.75, 1, 1.5, 2, 2.5, 3,4,5,6,8,12,16,24,48 and 72 hr after the last dose. Cardiovascular observations consisting of systolic and diastolic blood pressure and HR were measured using digital blood pressure cuffs before dosing from the first to the fifth dose and at 0, 2, 4, 8, 12, 24, 48 and 72 hr after the last dose.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the proposed model uses a concept of a set point, a reference value of MAP that can be lowered by a drug through TPR and assumes that a difference between current MAP and the set point acts as the driving force of exerting negative feedback to PP and HR. This idea of the set point being lowered by a drug is found in the literature in the case of losartan which has the same angiotensin II AT1 receptor-blocking mechanism as telmisartan [8] and enalapril which is an angiotensin-converting enzyme inhibitor [9].The objective of the current report was to improve upon empirical models to achieve better predictive capabilities using non-invasive markers with known physiological and drug action mechanisms, which can be readily applicable in real clinical situations. …”
mentioning
confidence: 99%